Au-Fe3O4-C electrode sensor and its preparation method and application in detecting arsenic and antimony
The Au-Fe3O4-C electrode sensor prepared by one-step electrodeposition method combines the characteristics of metals Au and Fe3O4 to solve the problem that the prior art is difficult to detect arsenic and antimony at the same time, achieving high sensitivity and rapid electrochemical analysis effects.
Patent Information
- Application Number
- CN202411056637.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The existing detection methods are difficult to achieve rapid, accurate and simultaneous detection of arsenic and antimony in environmental media, and the traditional methods require high sample pretreatment and cannot meet the needs of large-scale, fast and accurate detection.
The Au-Fe3O4-C electrode sensor was prepared by one-step electrodeposition method. The electrochemical analysis of arsenic and antimony was achieved by combining the electrocatalytic properties of metal Au, the adsorption and redox activity of Fe3O4, and the conductivity of carbon fiber cloth or carbon paper.
It improves the sensitivity to electrochemical analysis of arsenic and antimony, and realizes the simultaneous quantitative analysis of arsenic and antimony in the mixed solution, which has the advantages of simple operation, fast detection, stable detection and material reuse.
Smart Images

Figure CN118883674B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of detection sensor preparation, and in particular relates to an Au-Fe3O4-C electrode sensor and a preparation method thereof and application in detecting arsenic and antimony. Background Art
[0002] Antimony (Sb) and arsenic (As) compounds coexist in the lithosphere. Large-scale mining of antimony ore will release a large amount of arsenic and antimony pollutants into the environment in various forms, causing groundwater and surface water pollution in the mining area and nearby areas. The polluted water enters the soil or riverbed mud through adsorption, precipitation, biological absorption, etc., and then transfers to the human body through the food chain, posing a serious threat to the life and health of local residents. At present, the World Health Organization (WHO) has set a maximum limit of 10μg·L for As in drinking water. -1 The maximum limit of Sb is 5μg·L -1 As and Sb are in the same group in the periodic table, with the same atomic orbitals, similar physicochemical properties and toxicity mechanisms. They mainly exist in the environment in trivalent and pentavalent inorganic forms. The toxicity of trivalent compounds is much greater than that of pentavalent compounds, and they are carcinogenic, teratogenic and mutagenic to animals, plants and humans. Therefore, studying and monitoring the forms and contents of As and Sb in environmental media are of great significance to environmental regulation and human health.
[0003] The traditional method for As and Sb morphological analysis is a combination of high performance liquid chromatography (HPCL) and atomic mass spectrometry (AMS), atomic fluorescence spectrometry (AFS), and atomic absorption spectrometry (AAS). These methods have high requirements for sample pretreatment and cannot achieve on-site detection. Environmental samples need to be collected, stored, and transported to the laboratory in the field. The integrity of the As and Sb morphology is easily destroyed in any link of sample preparation, separation, and detection, and cannot meet the needs of large-scale, rapid, and accurate detection of As and Sb morphology in environmental media. Commonly used As and Sb on-site analysis methods include fluorescence, colorimetry, surface enhanced Raman spectroscopy, and electrochemical methods. The first three are mainly suitable for analyzing the morphology of organic compounds, and are not stable and accurate enough for trace detection of inorganic substances. In comparison, the electrochemical method achieves rapid and highly sensitive quantitative analysis of As and Sb by monitoring the current changes during the redox transformation of As and Sb, and has better application prospects in the field of morphological analysis of variable valence metal ions such as As and Sb.
[0004] Electrode sensor performance is the key to determining the effect of electrochemical analysis. Pooja Devi et al. synthesized rGO / Fe3O4 nanocomposites (NCs) using a chemical reduction method, used NCs-modified glassy carbon electrode (GCE) as the working electrode, and used square wave anodic stripping voltammetry (SWASV) to detect As in water with a sensitivity of 0.281 μA / μg·L -1, the limit of detection (LOD) is 0.12μg·L -1 .Samuel A heterostructure based on aminated multi-walled carbon nanotubes and gold nanoparticles was studied. -1 To 170.00μg·L -1 The detection limit of arsenite was 0.39 μg·L -1 , the recovery rate exceeded 99.1%. Lin Cui et al. assembled the unlabeled Ars-3 aptamer on the screen-printed carbon electrode (SPCE) through Au-S bonds. Ars-3 adsorbed polydiallyldimethylammonium (PDDA) through electrostatic interaction. Arsenite formed a complex with Ars-3, resulting in a decrease in the amount of PDDA adsorbed, thereby adsorbing the positively charged electrochemical active indicator [Ru(NH3)6] 3+ , the detection limit of arsenite is as low as 0.15nM. Liu used ionic liquid, graphene and nano-gold to modify selenium-doped carbon paste electrode to establish a differential pulse stripping voltammetry method for the determination of Sb. The detection limit of this method for Sb(III) is 2.7×10 -8 mol / L. Previous studies have achieved electrochemical detection of As or Sb by developing highly active electrode sensors. However, electrode sensors and electrochemical analysis methods that can simultaneously detect As and Sb have not been reported. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes an Au-Fe3O4-C electrode sensor and a preparation method thereof and application in detecting arsenic and antimony.
[0006] To achieve the above object, the present invention provides a method for preparing an Au-Fe3O4-C electrode sensor, comprising the following steps:
[0007] Carbon fiber cloth or carbon paper is used as the working electrode, Ag / AgCl is used as the reference electrode, Pt wire is used as the counter electrode, NaClO4 solution, Au 3+ Solution and Fe 3+ The mixed solution of the solutions is used as electrolyte, and the Au-Fe3O4-C electrode sensor is prepared by a one-step electrodeposition method.
[0008] Furthermore, the deposition potential of the one-step electrodeposition method is -1.0 to -1.2 V, and the deposition time is 30 to 60 s.
[0009] Furthermore, the concentration of the NaClO4 solution in the electrolyte is 12 to 15 g·L -1 , Au 3+ The concentration of the solution is 35-45 g·L -1 , Fe 3+The concentration of the solution is 130-140 g·L -1 ; The NaClO4 solution, Au 3+ Solution and Fe 3+ The volume ratio of the solution is 9.7:0.1:0.2.
[0010] Furthermore, the Au 3+ The solution is HAuCl4 solution, the Fe 3+ The solution is FeCl3 solution.
[0011] Furthermore, the carbon fiber cloth or carbon paper needs to be ultrasonically cleaned and ultraviolet dried before being used as a working electrode. More specifically, the pretreatment includes treating the CFC with HNO3 solution in an ultrasonic bath for 15 to 30 minutes, then rinsing in acetone, ethanol and deionized water for 5 to 10 minutes, and then drying by ultraviolet irradiation.
[0012] Furthermore, the concentration of the HNO3 solution is 20-40wt%.
[0013] The present invention also provides an Au-Fe3O4-C electrode sensor prepared by the preparation method.
[0014] The present invention also provides the application of the Au-Fe3O4-C electrode sensor in detecting trace arsenic forms. Before detection, As(V) is reduced to As(III) by ascorbic acid at 70°C. The electrochemical method used in the detection process is a square wave voltammetric anodic stripping method. The deposition voltage of the electrochemical method is -0.2 to -0.5V, the deposition time is 30 to 90s, and the stripping voltage is -0.4 to 0.4V.
[0015] The present invention also provides the application of the Au-Fe3O4-C electrode sensor in detecting the form of trace antimony. Before detection, Sb(V) is first reduced to Sb(III) by KI and VC. The electrochemical method used in the detection process is differential pulse voltammetry anodic stripping method. The deposition voltage of the electrochemical method is -0.2 to -0.5V, the deposition time is 30 to 90s, and the stripping voltage is -0.3 to 0.3V.
[0016] The present invention also provides the application of the Au-Fe3O4-C electrode sensor in the simultaneous detection of trace arsenic and trace antimony. The electrochemical method used in the detection process is a differential pulse voltammetric anodic stripping method. The deposition voltage of the electrochemical method is -0.2 to -0.5V, the deposition time is 30 to 90s, and the stripping voltage is -0.4 to 0.3V.
[0017] Compared with the prior art, the present invention has the following advantages and technical effects:
[0018] (1) The present invention prepares a composite Au-Fe3O4-C electrode sensor by electrodeposition, and combines the superior electrocatalytic performance of metal Au, the adsorption and redox activity of Fe3O4 on oxygen-containing anions As and Sb, and the good tolerance and conductivity of carbon fiber cloth or carbon paper to improve the sensitivity of electrochemical analysis of As and Sb. Using the Au-Fe3O4-C electrode sensor as the working electrode, differential pulse anodic stripping voltammetry is used, and the anodic stripping peak is fitted by Peak fit software, thereby achieving simultaneous quantitative analysis of As and Sb in the mixed solution.
[0019] (2) The present invention prepares a stable Au-Fe3O4-C electrode sensor material, and uses it as a working electrode to study the content of arsenic and antimony in water samples, and constructs an electrochemical rapid detection method for trace arsenic and antimony in natural water. The method of the present invention has the advantages of simple operation, rapid and stable detection, and the ability to reuse materials. It provides a rapid, sensitive and efficient detection method for the quantitative and qualitative analysis of trace arsenic and antimony in natural water, and plays an important role in environmental monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0021] Figure 1 The scanning electron microscope (SEM) images and element distribution diagrams of the CFC working electrode used in Example 1 and the Au-Fe3O4-C electrode sensor prepared in Example 1, wherein (a) is the SEM image of the CFC working electrode used in Example 1, (b)-(c) are SEM images of the Au-Fe3O4-C electrode sensor prepared in Example 1 at different magnifications, and (d)-(h) are element distribution diagrams of the Au-Fe3O4-C electrode sensor prepared in Example 1;
[0022] Figure 2 The XPS analysis results of the Au-Fe3O4-C electrode sensor prepared in Example 1, wherein (a) is the full XPS spectrum of Au-Fe3O4-C, (b) is the high-resolution XPS spectrum of C, (c) is the high-resolution XPS spectrum of Au, and (d) is the high-resolution XPS spectrum of Fe;
[0023] Figure 3 (a) is the SWV spectrum of the As(III) solution on the Au-Fe3O4-C electrode sensor prepared in Example 1, and (b) is the linear relationship between the As(III) concentration and the peak current of the anodic dissolution;
[0024] Figure 4(a) is the SWV spectrum of the As(V) solution on the Au-Fe3O4-C electrode sensor prepared in Example 1, and (b) is the linear relationship between the As(V) concentration and the peak current of the anodic dissolution;
[0025] Figure 5 (a) is a DPV spectrum of the Sb(III) solution on the Au-Fe3O4-C electrode sensor prepared in Example 1, and (b) is a linear relationship diagram between the Sb(III) concentration and the anodic dissolution peak current;
[0026] Figure 6 (a) is a DPV spectrum of Sb(V) solution on the Au-Fe3O4-C electrode sensor prepared in Example 1, and (b) is a linear relationship diagram between Sb(V) concentration and anodic dissolution peak current;
[0027] Figure 7 (a) is the DPV spectra of mixed standard solutions of As(III) and Sb(III) of different concentrations on the Au-Fe3O4-C electrode sensor prepared in Example 1, (b) is the DPV spectrum peak analysis diagram of the As(III) / Sb(III) mixed solution and the DPV spectra of pure As(III) and Sb(III) solutions, (c) is the linear relationship between the As(III) concentration and the peak current, and (d) is the linear relationship between the Sb(III) concentration and the peak current;
[0028] Figure 8 The Au-Fe3O4-C electrode sensor prepared in Example 1 detects As(III) and Sb(III) in the coexisting solution;
[0029] Fig. 9 (a) is the SWV spectrum of the As(III) solution on the Au-Fe3O4-C electrode sensor prepared in Example 2, and (b) is the linear relationship between the As(III) concentration and the peak current of the anodic dissolution;
[0030] Fig.10 (a) is the DPV spectrum of the Sb(III) solution on the Au-Fe3O4-C electrode sensor prepared in Example 2, and (b) is the linear relationship between the Sb(III) concentration and the anodic dissolution peak current. DETAILED DESCRIPTION
[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0032] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] The embodiment of the present invention provides a method for preparing an Au-Fe3O4-C electrode sensor, comprising the following steps:
[0037] Carbon fiber cloth (CFC) or carbon paper was used as the working electrode, Ag / AgCl as the reference electrode, Pt wire as the counter electrode, NaClO4 solution, Au 3+ Solution and Fe 3+ The mixed solution of the solutions is used as electrolyte, and the Au-Fe3O4-C electrode sensor is prepared by a one-step electrodeposition method.
[0038] In a preferred embodiment of the present invention, the deposition potential of the one-step electrodeposition method is -1.0 to -1.2 V, and the deposition time is 30 to 60 s.
[0039] In a preferred embodiment of the present invention, the concentration of the NaClO4 solution in the electrolyte is 12-15 g·L -1 , Au 3+ The concentration of the solution is 35-45 g·L -1 , Fe 3+The concentration of the solution is 130-140 g·L -1 ; The NaClO4 solution, Au 3+ Solution and Fe 3+ The volume ratio of the solution is 9.7:0.1:0.2.
[0040] In a preferred embodiment of the present invention, the Au 3+ The solution is HAuCl4 solution, the Fe 3+ The solution is FeCl3 solution.
[0041] In a preferred embodiment of the present invention, the carbon fiber cloth or carbon paper needs to be subjected to ultrasonic cleaning and ultraviolet drying treatment before being used as a working electrode, which specifically includes the following steps:
[0042] The carbon fiber cloth or carbon paper was treated with 40 wt % HNO 3 solution in an ultrasonic bath for 30 min, then rinsed in acetone, ethanol and deionized water for 10 min in sequence, and then dried by UV irradiation.
[0043] The embodiment of the present invention also provides an Au-Fe3O4-C electrode sensor prepared by the preparation method.
[0044] The sources of purchase of the raw materials used in the embodiments of the present invention are as follows:
[0045] Carbon fiber cloth (CFC), sodium perchlorate (NaCIO4), acetone, nitric acid (40wt% HNO3), hydrochloric acid, chloroauric acid (HAuCl4·H2O) and ascorbic acid were purchased from Sinopharm Chemical Reagent Co., Ltd., with a purity greater than 99.0%. Anhydrous ethanol, potassium iodide and ferric chloride (FeCl3·6H2O) were purchased from Shanghai McLean Biochemical Technology Co., Ltd., with a purity greater than 99.0%. The experimental water was DI pure water (resistivity ≥ 18.2MΩ·cm), prepared by Master Evo-S45UV ultrapure water system (Shanghai Hetai Instrument Co., Ltd.).
[0046] The electrochemical detection experiment used the Swiss Metrohm MultiAutolab / M204 multi-channel electrochemical workstation.
[0047] 1.00g·L -1 The standard stock solution of As(III) was purchased from Beijing North Weiye Metrology Technology Research Institute and stored in a dark place at 4℃; other concentrations of As(III) working solution were obtained by diluting the stock solution. Aqua regia was prepared by mixing concentrated hydrochloric acid and concentrated nitric acid in a ratio of 3:1 (volume ratio).
[0048] All glassware used in the examples were soaked in aqua regia and then cleaned with ultrapure water.
[0049] The chemical composition and existence form of the elements in the composite materials were analyzed using the Escalab250Xi X-ray photoelectron spectrometer (XPS) produced by Thermo Fisher Scientific.
[0050] The technical solution of the present invention is further illustrated by the following embodiments.
[0051] Example 1
[0052] A method for preparing an Au-Fe3O4-C electrode sensor comprises the following steps:
[0053] CFC was treated with 40 wt% HNO3 solution in an ultrasonic bath for 30 min, then rinsed in acetone, ethanol and deionized water for 10 min, and then dried by ultraviolet irradiation to obtain CFC as the working electrode, Ag / AgCl as the reference electrode, Pt wire as the counter electrode, and the electrolyte used was 9.7 mL of 14 g·L -1 NaClO4 solution, 0.1mL concentration is 41.2g·L -1 HAuCl4 solution and 0.2mL of 135.1g·L -1 The Au-Fe3O4-C electrode sensor was synthesized by mixing the Au and FeCl3 solutions at a deposition potential of -1.2 V and a deposition time of 30 s using a one-step electrodeposition method.
[0054] The scanning electron microscope (SEM) image of the CFC working electrode used in Example 1, the scanning electron microscope (SEM) image of the Au-Fe3O4-C electrode sensor prepared in Example 1 and the element distribution map are shown in FIG. Figure 1 , wherein (a) is the SEM image of the CFC working electrode used in Example 1, (b)-(c) are SEM images of the Au-Fe3O4-C electrode sensor prepared in Example 1 at different magnifications, and (d)-(h) are element distribution images of the Au-Fe3O4-C electrode sensor prepared in Example 1. Figure 1 (a) It can be seen that the original conductive carbon cloth has a three-dimensional network structure, which is composed of multiple fibers interlaced with each other, and the fiber surface is smooth; after electrodeposition treatment, the fiber surface becomes rough, like a dense white film, such as Figure 1 (b) Figure 1 (c) is a high-resolution SEM image of the composite fiber membrane, which shows that the fiber surface is tightly coated with nanoparticles. These nanoparticles are spherical and have a relatively uniform particle size. Figure 1 (d)-(h) are element distribution diagrams of nanoparticles on the fiber surface, confirming that the nanoparticles are composed of Au and Fe elements and that the nanoparticles are successfully loaded on the surface of the conductive carbon cloth.
[0055] In order to study the surface composition of the Au-Fe3O4-C electrode sensor prepared in Example 1 and the valence states of Au and Fe, an X-ray photoelectron spectroscopy (XPS) analysis was performed. The results are shown in Figure 2 ,From the XPS full spectrum analysis, we can see the characteristic peaks of C, O, Au and Fe elements, indicating that the Au-Fe3O4-C electrode sensor is composed of these four elements. Figure 2 (a) is the full XPS spectrum of Au-Fe3O4-C. Figure 2 (b) is the high-resolution XPS spectrum of C. The main peak at 284.8 eV is the CC bond, proving the existence of conductive carbon cloth. Figure 2 (c) is the high-resolution XPS spectrum of Au. The two main peaks at 88.0 eV and 84.4 eV correspond to Au 0 4f 5 / 2 and Au 0 Au4f 7 / 2 , indicating that Au in the nanoparticles deposited on the surface of the carbon cloth exists in the form of a single metal. Figure 2 (d) is the high-resolution XPS spectrum of Fe. The two peaks at 723.1 eV and 710.3 eV correspond to Fe 2+ 2p 1 / 2 and Fe 2+ 2p 3 / 2 The two peaks at 725.6eV and 712.4eV correspond to Fe 3+ 2p 1 / 2 and Fe 3+ 2p 3 / 2 , indicating that Fe in the nanoparticles exists in the form of Fe3O4 with multiple valence states.
[0056] Application Example 1
[0057] Using an electrochemical workstation (Autolab) three-electrode system, with test programs such as DPV and SWV, the type of acid (sulfuric acid, hydrochloric acid) and concentration (0.5M, 1M), deposition time (30s, 60s, 90s, 120s, 150s), deposition voltage (0.2v, 0.4v, 0.6v, 0.8v), etc. were adjusted to obtain the optimal test method for As(III), Sb(III), As(V), Sb(V) and their coexistence state, and standard solutions of As(III), Sb(III), As(V), and Sb(V) of different concentrations were prepared to detect the electrochemical performance of the Au-Fe3O4-C electrode sensor prepared in Example 1.
[0058] 1. Application of Au-Fe3O4-C electrode sensor in arsenic (As)
[0059] Prepare As(III) standard solutions of different concentrations. Figure 3 (a) is the square wave voltammetric stripping (SWV) spectra of As(III) solutions with concentrations of 1, 5, 10, 20, 50, 100, 200, 500, and 1000 μg / L on the Au-Fe3O4-C electrode sensor. After parameter optimization, it was found that when the deposition voltage was -0.4 V, the deposition time was 60 s, and the stripping voltage was -0.4 to 0.4 V, the electrochemical signal of As(III) was the highest. Figure 3 As shown in the SWV spectrum of (a), there is a strong anodic dissolution peak at a voltage of 0.18 V, which is the oxidation peak of As(0). As the As(III) concentration increases from 0 μg / L to 1000 μg / L, the peak intensity of the As(0) oxidation peak at 0.18 V gradually increases. Figure 3 (b) is the linear relationship between As(III) concentration and anodic dissolution peak current. It can be seen that the peak current of As(0) oxidation peak is linearly correlated with As(III) concentration. The corresponding regression equation is y=9E-07x+77E-05, and the determination coefficient (R 2 ) was 0.997, and the correlation coefficient (P) was less than 0.0001. The detection limit (LOD) was calculated based on 3δ / N, where δ was the standard deviation of 10 blank tests and N was the slope of the linear fitting equation. The theoretical LOD for the detection of As(III) by Au-Fe3O4-C electrode was 0.92 μg / L.
[0060] Due to the poor electrochemical activity of As(V), As(V) needs to be reduced to As(III) by ascorbic acid at 70 °C. Figure 4 (a) SWV spectra of As(V) solutions with concentrations of 20, 50, 100, 200, 300, 400, 500, and 1000 μg / L on the Au-Fe3O4-C electrode sensor. It can be seen that when the deposition voltage is -0.4 V and the deposition time is 60 s, the stripping is carried out between -0.4 and 0.5 V. There is a strong anodic stripping peak at 0.23 V in the SWV spectrum, which is the oxidation peak of As(0). Compared with the SWV spectrum of As(III), the peak position of the As(0) oxidation peak shifts positively, which is affected by the binding of ascorbic acid. The binding of ascorbic acid to As increases the oxidation potential of As(0) to As(III). As the As(V) concentration increases from 20 μg / L to 1000 μg / L, the peak intensity of the As(0) oxidation peak at 0.15 V gradually increases. The linear relationship between As(V) concentration and anodic dissolution peak current is shown in Figure 4 (b), the corresponding regression equation is y = 1.84E-7x + 8.23E-6, and the coefficient of determination (R 2) was 0.996, and the correlation coefficient (P) was less than 0.0001. The detection limit (LOD) was calculated based on 3δ / N, where δ was the standard deviation of 10 blank tests and N was the slope of the linear fitting equation. The theoretical LOD of the Au-Fe3O4-C electrode for As(V) detection was 0.12μg / L.
[0061] 2. Application of Au-Fe3O4-C electrode sensor in antimony (Sb)
[0062] Figure 5 (a) shows the differential pulse voltammetric stripping (DPV) spectra of Sb(III) solutions with concentrations of 1, 5, 10, 20, 50, 100, 200, 500, and 1000 μg / L on the Au-Fe3O4-C electrode. After parameter optimization, it was found that the electrochemical signal of Sb(III) was the highest when the deposition voltage was -0.4 V, the deposition time was 60 s, and the stripping voltage was -0.4 to 0.4 V. In the DPV spectrum, there is a strong anodic stripping peak at a voltage of 0.09 V, which is the oxidation peak of Sb(0). As the Sb(III) concentration increases from 0 μg / L to 1000 μg / L, the peak intensity of the Sb(0) oxidation peak at 0.09 V gradually increases. The actual detection limit of this method for Sb(III) is 1.0 μg / L. The linear relationship between Sb(III) concentration and the peak current of the anodic stripping peak is shown in Figure 5 (b), the corresponding regression equation is y = 4E-06x + 2E-04, and the coefficient of determination (R 2 ) was 0.980, and the correlation coefficient (P) was less than 0.0001. The limit of detection (LOD) was calculated based on 3δ / N, where δ was the standard deviation of 10 blank tests and N was the slope of the linear fitting equation. The theoretical LOD for the detection of Sb(III) by Au-Fe3O4-C electrode was 1.21 μg / L.
[0063] Due to the poor electrochemical activity of Sb(V), Sb(V) needs to be reduced to Sb(III) by 0.2 M potassium iodide and 0.05 M L (+)-ascorbic acid. Figure 6(a) DPV spectra of Sb(V) solutions with concentrations of 10, 20, 50, 100, 200, 300, 400, 500, and 1000 μg / L on Au-Fe3O4-C electrode. It can be seen that when the deposition voltage is -0.4 V and the deposition time is 60 s, dissolution and stripping occurs between -0.4 and 0.5 V, and there is a strong anodic dissolution peak at 0.23 V, which is the oxidation peak of Sb(0). Compared with the DPV curve of Sb(III), the anodic dissolution peak of Sb(V) moves from 0.09 V to -0.05 V in the opposite direction, which may be due to the presence of VC. VC combined with As reduces the oxidation potential of Sb(0) to Sb(III). As the concentration of Sb(V) increases from 0 μg / L to 1000 μg / L, the peak intensity of the Sb(0) oxidation peak at -0.15 V gradually increases. The linear relationship between Sb(V) concentration and anodic dissolution peak current is shown in Figure 6 (b), the corresponding regression equation is y = 3.78E-6x-4.72E-5, and the coefficient of determination (R 2 ) was 0.976, and the correlation coefficient (P) was less than 0.0001. The limit of detection (LOD) was calculated based on 3δ / N, where δ was the standard deviation of 10 blank tests and N was the slope of the linear fitting equation. The theoretical LOD for the detection of Sb(V) by Au-Fe3O4-C electrode was 6.47μg / L.
[0064] 3. AuFe@FeO x Application of electrode sensors in simultaneous detection of antimony (Sb) and arsenic (As)
[0065] In order to evaluate the AuFe@FeO x The electrochemical analysis technology of the electrode sensor can detect the ability of Sb(III) and As(III) at the same time. 1M HCl and different amounts of As(III) and Sb(III) are mixed in equal concentrations and volumes to prepare a 1:1 mass concentration As(III) and Sb(III) mixed standard solution with a concentration range of 1μg / L to 1mg / L. Differential pulse anodic stripping voltammetry is used. When the deposition voltage is -0.4V and the deposition time is 60s, stripping is carried out between -0.4 and 0.3V.
[0066] Figure 7 (a) is the DPV spectrum of mixed standard solutions of As(III) and Sb(III) with different concentrations on the Au-Fe3O4-C electrode sensor. It can be seen that an asymmetric anodic dissolution peak appears at a voltage of 0.1 V. As the concentration of the mixed solution of As(III) and Sb(III) increases from 1 μg / L to 1 mg / L, the peak value of the asymmetric peak gradually increases. Figure 7(b) is the DPV spectrum peak analysis diagram of the As(III) / Sb(III) mixed solution and the DPV spectra of pure As(III) and Sb(III) solutions. The anodic dissolution peak was separated by Peakfit software, and the asymmetric peak can be divided into two symmetrical peaks located at 0.02V and 0.09V respectively. 500μg / L As(III) solution and 500μg / L Sb(III) solution were tested by the DPV method. It was found that the anodic dissolution peak of As(III) under the DPV mode was located at 0.02V, and the anodic dissolution peak of Sb(III) was located at 0.09V. The DPV spectra of mixed solutions of As(III) and Sb(III) with different concentrations were separated, and a standard curve was established between the peak area of the anodic dissolution peak at 0.02V and the As(III) concentration ( Figure 7 (c) in the figure, the corresponding regression equation is y = 0.1665x-2.7638, and the coefficient of determination (R 2 ) is 0.971, and the correlation coefficient (P) is less than 0.0001; the peak area of the anodic dissolution peak at 0.09 V is also linearly correlated with the Sb(III) concentration ( Figure 7 (d) in the figure, the corresponding regression equation is y = 0.2898x-0.8918, and the coefficient of determination (R 2 ) is 0.983, and the correlation coefficient (P) is less than 0.0001. It can be determined that the DPV method based on Au-Fe3O4-C electrode sensor can simultaneously analyze As(III) and Sb(III) in the sample.
[0067] Application Example 2
[0068] 1. Anti-interference performance
[0069] In order to investigate the interference of common metal ions in water on the detection of As(III) and Sb(III) by Au-Fe3O4-C electrode sensor, 100 μg / L CaCl2, CdCl2, CuSO4, FeCl3, KCl, MgCl2, MnCl2 solutions and 50 μg / L Na2CO3 solutions were prepared respectively and mixed with 20 μg / L As(III) and Sb(III) to obtain coexistence solutions. The Au-Fe3O4-C electrode sensor prepared in Example 1 was used to detect As(III) and Sb(III) in the coexistence solutions. The results are shown in Table 1. Figure 8 , it can be seen that 100μg / L Ca 2+ 、Cd 2+ , Cu 2+ , Fe 3+ , K + Mg 2+ , Mn 2+ 、Na +There was no obvious interference with the detection of 20μg / LAs(Ⅲ) and Sb(III).
[0070] 2. Stability
[0071] The same Au-Fe3O4-C electrode sensor prepared according to Example 1 was used to continuously measure 100 μg / L As(III) and Sb(III) for 10 times, showing that the relative standard deviation (RSD) of the peak current was 3.7%. According to the method of Example 1, 10 Au-Fe3O4-C electrode sensors were prepared in parallel, and 100 μg / L As(III) and Sb(III) were measured. The relative standard deviation of the peak current was 4.6%. The results show that the Au-Fe3O4-C electrode sensor prepared by the present invention has good repeatability and reproducibility. The Au-Fe3O4-C electrode sensor was stored at room temperature for 7 days, and the same concentration of As(III) and Sb(III) was measured. The dissolution peak current response remained basically unchanged. After 21 days of storage, it can still maintain 88% of the initial response, indicating that the Au-Fe3O4-C electrode sensor has good stability.
[0072] Example 2
[0073] A method for preparing an Au-Fe3O4-C electrode sensor comprises the following steps:
[0074] CFC was treated with 40 wt% HNO3 solution in an ultrasonic bath for 30 min, then rinsed in acetone, ethanol and deionized water for 10 min, and then dried by ultraviolet irradiation to obtain CFC as the working electrode, Ag / AgCl as the reference electrode, Pt wire as the counter electrode, and the electrolyte used was 9.7 mL of 14 g·L -1 NaClO4 solution, 0.1mL concentration is 41.2g·L -1 HAuCl4 solution and 0.2mL of 135.1g·L -1 The Au-Fe3O4-C electrode sensor was synthesized by mixing the Au-Fe3O4-C electrode with the FeCl3 solution and the deposition time of 60s at a deposition potential of -1.0V using a one-step electrodeposition method.
[0075] Application Example 3
[0076] The application method of the Au-Fe3O4-C electrode sensor of Example 2 in arsenic (As) and antimony (Sb) is the same as that of Application Example 1.
[0077] Fig. 9(a) is the square wave voltammetric stripping (SWV) spectrum of As(III) on the Au-Fe3O4-C electrode sensor prepared in Example 2. It can be seen that there is a strong anodic stripping peak at 0.18 V, which is the oxidation peak of As(0). As the concentration of As(III) increases from 10 μg / L to 1000 μg / L, the peak intensity of the As(0) oxidation peak at 0.18 V gradually increases. Fig. 9 (b) is the linear relationship between As(III) concentration and anodic dissolution peak current. It can be seen that the peak current of As(0) oxidation peak is linearly correlated with As(III) concentration. The corresponding regression equation is y=1.3E-7x+5.6E-6, and the determination coefficient (R 2 ) is 0.997, and the correlation coefficient (P) is less than 0.0001.
[0078] Fig.10 (a) is the differential pulse voltammetric stripping (DPV) spectrum of Sb(III) on the Au-Fe3O4-C electrode prepared in Example 2. It can be seen that there is a strong anodic stripping peak at 0.09V, which is the oxidation peak of Sb(0). As the Sb(III) concentration increases from 10μg / L to 500μg / L. The linear relationship between Sb(III) concentration and anodic stripping peak current is shown in Fig.10 (b), the corresponding regression equation is y = 1.5E-6x + 6E-5, and the coefficient of determination (R 2 ) is 0.994, and the correlation coefficient (P) is less than 0.0001.
[0079] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing an Au-Fe3O4-C electrode sensor, characterized in that: The following steps are involved: Carbon fiber cloth or carbon paper is used as the working electrode, Ag / AgCl is used as the reference electrode, Pt wire is used as the counter electrode, NaClO4 solution, Au 3+ Solution and Fe 3+ The mixed solution of the solution is used as an electrolyte, and the Au-Fe3O4-C electrode sensor is prepared by a one-step electrodeposition method; The deposition potential of the one-step electrodeposition method is -1.0 to -1.2 V, and the deposition time is 30 to 60 s; The concentration of NaClO4 solution in the electrolyte is 12-15 g·L -1 , Au 3+ The concentration of the solution is 35-45 g·L -1 , Fe 3+ The concentration of the solution is 130-140 g·L -1 ; The NaClO4 solution, Au 3+ Solution and Fe 3+ The volume ratio of the solution is 9.7:0.1:0.
2.
2. The method for preparing the Au-Fe3O4-C electrode sensor according to claim 1, characterized in that: The carbon fiber cloth or carbon paper also includes a pretreatment step before use; the pretreatment includes treating the CFC with HNO3 solution in an ultrasonic bath for 15 to 30 minutes, then rinsing in acetone, ethanol and deionized water for 5 to 10 minutes in sequence, and then drying by ultraviolet irradiation.
3. The method for preparing the Au-Fe3O4-C electrode sensor according to claim 2, characterized in that: The concentration of the HNO3 solution is 20-40 wt%.
4. An Au-Fe3O4-C electrode sensor prepared by the preparation method according to any one of claims 1 to 3.
5. The use of the Au-Fe3O4-C electrode sensor as claimed in claim 4 in detecting trace arsenic forms, characterized in that: Before detection, As(V) was reduced to As(III) by ascorbic acid at 70°C. The electrochemical method used in the detection process was a square wave voltammetric anodic stripping method. The deposition voltage of the electrochemical method was -0.2 to -0.5V, the deposition time was 30 to 90s, and the stripping voltage was -0.4 to 0.4V.
6. The use of the Au-Fe3O4-C electrode sensor in detecting trace antimony forms as claimed in claim 4, characterized in that: Before detection, Sb(V) is first reduced to Sb(III) by KI and VC. The electrochemical method used in the detection process is differential pulse voltammetry anodic stripping method. The deposition voltage of the electrochemical method is -0.2 to -0.5V, the deposition time is 30 to 90s, and the stripping voltage is -0.3 to 0.3V.
7. The use of the Au-Fe3O4-C electrode sensor as described in claim 4 in the simultaneous detection of trace arsenic and trace antimony, the electrochemical method used in the detection process is differential pulse voltammetry anodic stripping method, the deposition voltage of the electrochemical method is -0.2 to -0.5V, the deposition time is 30 to 90s, and the stripping voltage is -0.4 to 0.3V.
Citation Information
Patent Citations
Core-shell structure electrode material for arsenic-antimony electrochemical detection
CN111624243A